Early life thermal stress: Impact on future thermotolerance, stress response, behavior, and intestinal morphology in piglets exposed to a heat stress challenge during simulated transport1. (4th April 2018) - Johnson, Jay S; Aardsma, Matthew A; Duttlinger, Alan W; Kpodo, Kouassi R
Abstract: Study objectives were to evaluate the impact of early life thermal stress (ELTS ) on thermoregulation, stress response, and intestinal health of piglets subjected to a future heat stress (HS ) challenge during simulated transport. From d 7 to 9 post-farrowing, 12 first-parity sows and their litters were exposed to thermoneutral (ELTN ; 25.4 ± 1.1 °C w/heat lamp; n = 4), HS (ELHS ; cycling 32–38 °C w/heat lamp; n = 4), or cold stress (ELCS ; 25.4 ± 1.1 °C w/no heat lamp; n = 4) conditions, and then from d 10 until weaning all piglets were exposed to thermoneutral (TN ) conditions (25.3 ± 1.9 °C w/heat lamp). During the ELTS period, respiration rate, rectal temperature (T R ), and skin temperature (T S ) of three mixed-sex piglets per dam were monitored daily (0800, 1200, 1600, 2000 h). At 13 ± 1.3 d of age, temperature recorders were implanted intra-abdominally into all piglets. At weaning (20.0 ± 1.3 d of age), piglets were bled and then herded up a ramp into a simulated transport trailer and exposed to HS conditions (cycling 32–38 °C) for 8 h. During the 8 h simulated transport, core body temperature (T C ) and TS were assessed every 15 min. After the simulated transport, piglets were unloaded from the trailer, bled, weighed, and then housed individually in TN conditions (28.5 ± 0.7 °C) for 7 d. During this time, ADFI and ADG were monitored, blood samples were taken on d 1, 4, and 7, and piglets were video-recorded to assess behavior. Piglets were sacrificed on d 8 post-simulated transport and intestinal morphology was assessed. Data were analyzed using PROC MIXED in SAS 9.4. In the ELTS period, piglet TR was increased overall ( P = 0.01) in ELHS (39.77 ± 0.05 °C) compared to ELTN (39.34 ± 0.05 °C) and ELCS (39.40 ± 0.05 °C) litters. During simulated transport, TC was greater ( P = 0.02) in ELHS (40.84 ± 0.12 °C) compared to ELTN (40.49 ± 0.12 °C) and ELCS (40.39 ± 0.12 °C) pigs. Following simulated transport, BW loss was greater ( P = 0.01; 40%) for ELHS compared to ELTN and ELCS pigs and ADFI was reduced ( P = 0.05; 28.6%) in ELHS compared to ELTN pigs. Sitting behavior tended to be increased ( P = 0.06; 47.4%) in ELHS vs. ELCS or ELTN pigs. Overall, circulating cortisol was greater for ELHS ( P ≤ 0.01; 38.8%) compared to ELCS and ELTN pigs. Goblet cells per villi were reduced ( P = 0.02; 20%) in the jejunum of ELHS vs. ELCS and ELTN pigs. In summary, ELHS reduced thermotolerance and increased the future stress response of piglets compared to ELCS and ELTN.